2021
DOI: 10.1039/d0sc07052a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Lewis acid-bonded picolinaldehyde enables enantiodivergent carbonyl catalysis in the Mannich/condensation reaction of glycine ester

Abstract: The catalytic asymmetric Mannich/condensation of glycine ester with aldimines was achieved by merging chiral N,N′-dioxide/YbIII complex Lewis acid catalysis/carbonyl catalysis under mild condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…The chiral catalyst promoted reaction of 1q proceeded well, implying that the S N i mechanism is dominant, and the anion-involved S N 2 mechanism could be ruled out in this system, 17 and it is also different from previous intermolecular desymmetric processes. [6][7][8][9][10][11][12][13] Based on the absolute configuration of the product 2a and the single-crystal structure of the catalyst L 3 -RaEt 2 /Yb(OTf ) 3 , 18 possible work modes to unveil the enantiocontrol are provided in Scheme 3d. Initially, the chiral Yb(III) catalyst bonds 2-picolinoyl-aziridine 1a with the two nitrogens, and the pyridine ring is located above the bicyclic ring of the ligand where CH-π interaction could stabilize the state to extend based on our previous study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chiral catalyst promoted reaction of 1q proceeded well, implying that the S N i mechanism is dominant, and the anion-involved S N 2 mechanism could be ruled out in this system, 17 and it is also different from previous intermolecular desymmetric processes. [6][7][8][9][10][11][12][13] Based on the absolute configuration of the product 2a and the single-crystal structure of the catalyst L 3 -RaEt 2 /Yb(OTf ) 3 , 18 possible work modes to unveil the enantiocontrol are provided in Scheme 3d. Initially, the chiral Yb(III) catalyst bonds 2-picolinoyl-aziridine 1a with the two nitrogens, and the pyridine ring is located above the bicyclic ring of the ligand where CH-π interaction could stabilize the state to extend based on our previous study.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the chiral Yb(III) catalyst bonds 2-picolinoyl-aziridine 1a with the two nitrogens, and the pyridine ring is located above the bicyclic ring of the ligand where CH-π interaction could stabilize the state to extend based on our previous study. 18 The mode in the left was unfavorable due to the block raised from the lower left amide substitution of the ligand with the ring of 1a. Alternatively, the orientation of the substrate in the right mode has priority where the cyclic backbone of aziridine toward the groove between the downward amide and the bicyclic ring of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…nates. [13][14][15][16] By using chiral pyridoxals as catalysts, we have successfully developed asymmetric biomimetic Mannich reaction [13] and a-C Michael addition [14] of glycinate, respectively affording chiral a,b-diamino acid esters and pyroglutamic acid esters with excellent enantiopurities (Scheme 1 e). Herein, we reported the first catalytic asymmetric aldol reaction of glycinate with trifluoromethyl ketones (Scheme 1 f).…”
mentioning
confidence: 99%
“…nates. [13][14][15][16] By using chiral pyridoxals as catalysts, we have successfully developed asymmetric biomimetic Mannich reaction [13] and a-C Michael addition [14] of glycinate, respectively affording chiral a,b-diamino acid esters and pyroglutamic acid esters with excellent enantiopurities (Scheme 1 e). Herein, we reported the first catalytic asymmetric aldol reaction of glycinate with trifluoromethyl ketones (Scheme 1 f).…”
mentioning
confidence: 99%
“…Further screening showed that up to 80 % yield of the diastereomer syn-6 a, 9:1 dr, and 98 % ee were obtained when 0.2 equivalent of Tf 2 NH was used (Table 1, entry 10 vs. [3][4][5][6][7][8][9]. Dichloromethane (DCM) was the choice of solvent (Table 1, entry 11 vs. 3 and 12-15) and catalyst 7 a gave the best performance among the pyridoxals 7 a-f examined (Table 1, entry 11 vs. [16][17][18][19][20]. To our surprise, the reaction can also proceed smoothly without losing efficiency and selectivity when lowering the catalyst loading to 0.1 mol % (Table 1, entry 21 vs. 10).…”
mentioning
confidence: 99%